Investment externalities, bank liquidity creation, and bank failures - Diemo Dietrich; Uwe Vollmer (Journal of Economics, 2023)
Recent evidence suggests that banks are interconnected through investment externalities among their borrowers. We study how such investment externalities affect the ability of unregulated, competitive banks to facilitate risk sharing among bank depositors, adapting a canonical model of banks as creators of liquidity subject to fundamental risks to bank returns. Failures occur when banks become insolvent. We find that investment externalities render fundamental risks to bank returns endogenous, risk sharing among depositors inefficient, probabilities of bank failures too high, and payouts to depositors in the event of a bank failure too low. These effects arise because productivity is too low in the presence of investment externalities. Minimum liquidity standards and bank bailouts dampen productivity further.
Keywords: G21; G28; G33; O47; 330; Insolvency risk; Aggregate productivity; Bank bailouts